From the London evening post, 29th of April 1775. To the three generals, with Scotch orders, on their voyage to North-America : Critical and faithful extracts from Colonel Cavallier's Memoirs of the wars of the Cevennes, or Lower Languedoc, in his own handwriting, and in the French language - Cavalier, Jean, 1681-1740 (LLMC-digital (Series), 1775)
Drawing parallels between the persecution of the French Protestants as described by Cavalier, and Great Britain's policy toward the American colonies.